The influence of work commitment and job satisfaction on employee performance in construction companies at PT 'X' - Damayanti, Eka Ari; Sibarani, Mentiana (Indonesian Journal of Multidisciplinary Science, 2024)
The COVID-19 pandemic has had a significant impact on the construction industry in Indonesia, including the high employee turnover rate which has an impact on project productivity and quality. This study aims to analyze the influence of work commitment and job satisfaction on employee performance at PT "X". The method used was a quantitative approach with a random sampling technique, involving 287 employees as respondents. Data were obtained through questionnaires measured by the Likert scale, and analyzed using regression analysis and ANOVA. The results of the study show that both work commitment and job satisfaction significantly affect employee performance. The findings indicate that companies need to focus on increasing commitment and job satisfaction to lower turnover rates and increase productivity. This study implicates the need for companies to create a conducive work environment, provide attractive incentives, and provide career development opportunities so that employees feel more connected to the company. By increasing commitment and job satisfaction, it is hoped that PT "X" can achieve better performance and more stable project sustainability in the future.